Near infrared spectroscopy-guided exercise training for claudication in peripheral arterial disease. (29th August 2020) - Murrow, Jonathan R; Brizendine, Jared T; Djire, Bill; Young, Hui-Ju; Rathbun, Stephen; Nilsson, Kent R; McCully, Kevin K
Abstract: Rationale: Supervised treadmill exercise for claudication in peripheral arterial disease is effective but poorly tolerated because of ischemic leg pain. Near infrared spectroscopy allows non-invasive detection of muscle ischemia during exercise, allowing for characterization of tissue perfusion and oxygen utilization during training. Objective: We evaluated walking time, muscle blood flow, and muscle mitochondrial capacity in patients with peripheral artery disease after a traditional pain-based walking program and after a muscle oxygen-guided walking program. Method and results: Patients with peripheral artery disease trained thrice weekly in 40-minute-long sessions for 12 weeks, randomized to oxygen-guided training ( n = 8, age 72 ± 9.7 years, 25% female) versus traditional pain-based training ( n = 10, age 71.6 ± 8.8 years, 20% female). Oxygen-guided training intensity was determined by maintaining a 15% reduction in skeletal muscle oxygenation by near infrared spectroscopy rather than relying on symptoms of pain to determine exercise effort. Pain free and maximal walking times were measured with a 12-minute Gardner treadmill test. Gastrocnemius mitochondrial capacity and blood flow were measured using near infrared spectroscopy. Baseline pain-free walking time was similar on a Gardner treadmill test (2.5 ± 0.9 vs . 3.6 ± 1.0 min, p = 0.5). After training, oxygen-guided cohorts improved similar to pain-guided cohorts (pain-free walking time 6.7 ± 0.9 vs . 6.9 ± 1.1 min, p < 0.01 for change from baseline and p = 0.97 between cohorts). Mitochondrial capacity improved in both groups but more so in the pain-guided cohort than in the oxygen-guided cohort (38.8 ± 8.3 vs . 14.0 ± 9.3, p = 0.018). Resting muscle blood flow did not improve significantly in either group with training. Conclusions: Oxygen-guided exercise training improves claudication comparable to pain-based training regimens. Adaptations in mitochondrial function rather than increases in limb perfusion may account for functional improvement. Increases in mitochondrial oxidative capacity may be proportional to the degree of tissue hypoxia during exercise.